2021
DOI: 10.1016/j.jaad.2020.05.029
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of diagnosed acne and weight status in adolescent girls

Abstract: We analyzed a large, multicenter, retrospective cohort of 368 adult patients with SJS/TEN from the United States. 4 Of 314 patients known to survive to hospital discharge, 150 (47.8%) had information available regarding postdischarge follow-up. Of these, there was no mention of SJS/TEN-related sequelae in 54.7% (82/150), and long-term sequelae were noted in the remaining 45.3% (68/150), characterized as ocular, cutaneous, gastrointestinal, genital, renal, pulmonary, or other. Sequelae were reported to be seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, another study of 10 to 17-year-old girls did not find a higher prevalence of acne in overweight/obese girls >13 years old, 9 though it did in girls ages 10-12 years with higher BMI. 9 These prior studies were largely retrospective reviews without controls, highlighting the importance of the results of our true-population based study with case-controls. While acne severity was not assessed directly in our study, acne treatments used may serve as an indirect indicator of severity.…”
Section: Relationship Between Bmi and Acne In Children Ages 7 To ≤12 ...mentioning
confidence: 84%
See 3 more Smart Citations
“…However, another study of 10 to 17-year-old girls did not find a higher prevalence of acne in overweight/obese girls >13 years old, 9 though it did in girls ages 10-12 years with higher BMI. 9 These prior studies were largely retrospective reviews without controls, highlighting the importance of the results of our true-population based study with case-controls. While acne severity was not assessed directly in our study, acne treatments used may serve as an indirect indicator of severity.…”
Section: Relationship Between Bmi and Acne In Children Ages 7 To ≤12 ...mentioning
confidence: 84%
“…Two prior studies of children ages 6-11 years 12 and 7-19 years 7 found overweight/obesity to be risk factors for acne presence. However, another study of 10 to 17-year-old girls did not find a higher prevalence of acne in overweight/obese girls >13 years old, 9 though it did in girls ages 10-12 years with higher BMI. 9 These prior studies were largely retrospective reviews without controls, highlighting the importance of the results of our true-population based study with case-controls.…”
Section: Relationship Between Bmi and Acne In Children Ages 7 To ≤12 ...mentioning
confidence: 84%
See 2 more Smart Citations
“…The diagnostic potential of the hub genes was robustly validated by the ROC curve analysis across multiple datasets, consistently showing AUC values exceeding 90%. Such high diagnostic accuracy indicates their reliability as objective molecular markers, which could revolutionize acne assessment, transitioning from the traditional subjective visual grading to a more consistent molecular‐based approach 90 . This study's methodological rigor was further highlighted by the use of paired samples, which effectively countered interindividual variability, ensuring the credibility of the identified differentially expressed genes (DEGs).…”
Section: Discussionmentioning
confidence: 99%